Ranula, Its Etiopathogenesis And Management; A Systematic Review - Yadav, Ramanand; Tewari, Vertika (ENT Updates, 2021)
Ranula is defined as a swelling on the floor of the mouth, and its etiology is unclear. Aspects of etiopathogenesis, origin, and management remain debatable. The rationale of our study was to eliminate the discrepancies pertaining to the etiopathogenesis and management of ranula. Our objective was to determine the etiopathogenesis of ranula by systematically reviewing the available literature and to establish the best treatment protocol for ranula (intraoral and plunging). Case series, case reports, and observational and longitudinal studies referring to the etiology, pathogenesis, and management of ranula were included, and the previously published review articles were excluded from our study. We performed an electronic search from the year of inception of the database to December 2019. PubMed, Science direct, and Google Scholar databases were explored without restrictions of language or publication date. The search algorithm was Ranula Mesh Major topic and Etiopathogenesis, Ranula Mesh Major topic and Management. A total of 64 full-text articles were assessed. We concluded that the presence of the Bartholin duct might be a possible cause of intraoral ranula development, indicating that it originates from greater sublingual gland. Intraoral and plunging ranula are traumatic extravasation pseudocysts. Congenital ranula are histopathologically classified retention cysts lined with stratified squamous epithelium. The mylohyoid muscle exhibits dehiscence, which is commonly present in the anterior two-third part from which a part of the sublingual gland can be herniated or mucus can extravasate, leading to the formation of plunging ranula. Transoral excision with complete excision of ipsilateral sublingual gland remains the gold standard treatment of intraoral ranula and gold standard surgical treatment for plunging ranula. For mixed ranula, the treatment includes transoral excision of the sublingual gland along with the drainage of cyst.